Respuesta :

2(-6y)-9y = 14
-12y - 9y = 14
-21y = 14
y = -2/3

Answer:

(7,0) ---> (x = 7) and (y = 0)

Step-by-step explanation:

2x – 9y = 14

x= -6y +7     <-- (Substitute for x to above equation)

---------------------------------------------------------------------------------------------------------

2(-6y +7)– 9y = 14

-12y + 14 - 9y = 14    <-- combine like terms

-21y + 14 = 14  

        -14 = -14   <-- inverse operation on both sides

      -21y = 0     <-- Divide

          y = 0  <--- Substitute for y to get x  ↓

-------------------------------------------------------------------------------------------------------

2x – 9y = 14

2x – 9(0) = 14     <-- Substituted y from above

          2x = 14     <-- Divide

            x = 7